A model-based method to control temperature and humidity in intermittently heated massive historic buildings. (15th July 2019) - Wessberg, Magnus; Vyhlídal, Tomáš; Broström, Tor
Abstract: The indoor climate of historic buildings is governed not only by human comfort but also the desire to preserve these buildings and their interiors. For preservation, relative humidity is the most important parameter, including its amplitude and change rate. To control the change rate of relative humidity at a heat-up event for an intermittently heated massive historic building with heavy masonry walls, a simplified model for heat and moisture transfer at the heat-up time is presented. A method to derive the time constants and hygrothermal parameters of the building from measurements taken during a step response test is proposed and validated. The model with its parameters can be used to predict both heat-up time to reach the target temperature as well as the amount of moisture gained from the walls. These predictions are in turn used to calculate the decrease in relative humidity during the heat-up event. The indoor air relative humidity is predictable as it is determined by the air temperature and air mixing ratio. A control algorithm that uses the model for predicting and controlling the change rate of relative humidity by shaping the heating power is presented and validated using simulation results. Highlights: A model for heat and moisture transfer in intermittently heated historic building is presented. The model is applied to predict heat-up time to a target temperature. The relative humidity change rate is controlled by properly shaped heating power. The proposed model-based control procedure is easy to implement on a low-cost heating system.